Double Stent Retriever Technique for Mechanical Thrombectomy: A Systematic Review and Meta-Analysis - Hofmeister, Jeremy; Brina, Olivier; Bernava, Gianmarco; Rosi, Andrea; Reymond, Philippe; Lovblad, Karl-Olof; Machi, Paolo (American Journal of Neuroradiology, 2024)
BACKGROUND: Mechanical thrombectomy using a double stent retriever technique has recently been described for the treatment of acute ischemic stroke, but its efficacy and safety are not well-established.PURPOSE: The aim of this systematic review and meta-analysis was to evaluate reports of the use of a double stent retriever technique during the endovascular treatment of patients with ischemic stroke.DATA SOURCES: The PubMed, EMBASE, Web of Science, and Scopus databases were searched to identify all studies (clinical trials, cohort series, and case reports) investigating the utility of a double stent retriever technique for the treatment of stroke. The study is reported in accordance with PRISMA 2020 guidelines and was prospectively registered in PROSPERO (CRD42023482691).STUDY SELECTION: Seventeen studies involving a total of 128 patients with large-vessel occlusions predominantly in the anterior circulation (93.0%) were identified.DATA ANALYSIS: Outcomes of interest were the prevalence of successful recanalization (modified TICI ≥2b) and a first-pass effect following the double stent retriever technique as well as complications such as iatrogenic dissections and SAH. Data were pooled using a random effects model.DATA SYNTHESIS: The double stent retriever technique was used as a rescue strategy in occlusions refractory to conventional endovascular treatment in 68.7% (88/128) of patients and as a first-line strategy in 31.3% (40/128) of patients. The double stent retriever technique achieved an overall final modified TICI ≥2b in 92.6% cases, with a first-pass effect of 76.6%. The complication rate remained low, with 0.37% dissection and 1.56% SAH.LIMITATIONS: Limitations of the study include the following: 1) a large number of case reports or small series, 2) a meta-analysis of proportions with no statistical comparison with a control group, and 3) the lack of access to patient-level data.CONCLUSIONS: Our findings suggest that double stent retriever thrombectomy may be safe and associated with good recanalization outcomes, but prospective comparative studies are needed to determine which patients may benefit from this endovascular procedure.AICHasymptomatic intracranial hemorrhageAISacute ischemic strokeDSRdouble stent retrieverFPEfirst-pass effectMTmechanical thrombectomymTICImodified TICINOSNewcastle-Ottawa ScaleSICHsymptomatic intracranial hemorrhageSRstent retrieverSSRsingle stent retriever